OPTIMALISASI SDM MELALUI PENERAPAN PENDIDIKAN OTOMASI INDUSTRI DAN ROBOTIKA DI SMK - Ceng Saeful Ramdan; Hadfina Azra Syahidah; Mochamad Zulfikar; Naura Satira; Yusa Munggaran Antariksa; Rama Wijaya Abdul Rozak (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Industrial Automation engineering education at SMK aims to improve the quality of human resources in the field of technology. This study aims to analyze the process of optimizing human resources through industrial automation and robotics training at SMK. The method used is a survey by distributing questionnaires to students at SMKN 4 Bandung. The results of this study indicate that industrial automation and robotics training in secondary vocational schools plays an important role in the development of quality human resources. Apart from equipping students with high technical skills, this education also cultivates traits such as creativity, innovation, and collaboration. The positive impact of industrial automation and robotics engineering training in vocational schools will also help improve product quality and industrial productivity in the future. Therefore, we recommend continuing to develop and improve the teaching of industrial automation and robotics subjects in Vocational High Schools to improve the quality of human resources in the field of technology. By optimizing automation engineering education at Vocational High Schools, it is hoped that Vocational High School graduates will become competent and ready to work workers in the technology sector, and be able to contribute to improving product quality and industrial productivity in Indonesia. Improving the quality of human resources in the field of technology will also have a positive impact on the development of the national industrial sector, increase competitiveness in the global market, and have the potential to create better job opportunities for the community. Therefore, the development of automation engineering education in Vocational Schools needs to be continuously encouraged to respond to the challenges and needs of future technological developments.Â Â